Les archives nationales (Paris-Fontainebleau) : sources pour la connaissance du patrimoine bâti religieux, XIXe-XXe siècles - Nadine Gastaldi (In Situ)
Major archival items on religious buildings of the 19th and 20th centuries are kept in the French National Archives repositories in Paris and Fontainebleau. Their presentation gives an opportunity to withdraw the context in which these documents were issued by a great variety of producers. Beyond laws on public cults, issues on public property and architecture are indeed to be taken in account.